GAGASAN KONTEKSTUALISASI MODEL TERJEMAHAN DALAM PENGUATAN KATEKESE UMAT - Jelahu, Timotius Tote (SEPAKAT-Jurnal Pastoral Kateketik, 2016)
Originated from the Catholic Catechesis model that was developed by Indonesian Catholic Church, this article argues that the implementation of catechesis must bring the faithful to accept and understand the truth of the bible. The catechism model used should not obscure evangelical truth and faith inherited in the Catholic Church tradition. In this case, the translation model is a theological model that truly accepts the Bible and doctrinal traditions as being both contextual and complete. Therefore, the writer presents the Catecheticalâs development by taking positive values from the contextualization of the translation model.